al-Shaykh Nasir Abi Nabhan al-Kharusi, 1192-1262H fi atharihi al-lughawiyah - al-Rumhi, Ahmad ibn Muhammad (Masqat : Dhakirat'Uman, 2017)
Arabic language; Arab scholars; grammar; early works.
Includes bibliographical references (pages 117-123).
Keywords: al-Kharusi, Nasir; Arabic language -- Grammar -- Early works to 1800.